2021
DOI: 10.3389/fonc.2021.777849
|View full text |Cite
|
Sign up to set email alerts
|

A Review on the Role of AFAP1-AS1 in the Pathoetiology of Cancer

Abstract: AFAP1-AS1 is a long non-coding RNA which partakes in the pathoetiology of several cancers. The sense protein coding gene from this locus partakes in the regulation of cytophagy, cell motility, invasive characteristics of cells and metastatic ability. In addition to acting in concert with AFAP1, AFAP1-AS1 can sequester a number of cancer-related miRNAs, thus affecting activity of signaling pathways involved in cancer progression. Most of animal studies have confirmed that AFAP1-AS1 silencing can reduce tumor vo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 77 publications
2
7
0
Order By: Relevance
“…However, information regarding the role of LMNTD2‐AS1 and KLRK1‐AS1 in cancer development is still unknown. AFAP1‐AS1 is a rising star in lncRNA and its function has been summarized in some excellent reviews 33,50 . In our study, we found that AFAP1‐AS1 also has a metabolic impact on CRC.…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…However, information regarding the role of LMNTD2‐AS1 and KLRK1‐AS1 in cancer development is still unknown. AFAP1‐AS1 is a rising star in lncRNA and its function has been summarized in some excellent reviews 33,50 . In our study, we found that AFAP1‐AS1 also has a metabolic impact on CRC.…”
Section: Discussionsupporting
confidence: 57%
“…AFAP1‐AS1 is a rising star in lncRNA and its function has been summarized in some excellent reviews. 33 , 50 In our study, we found that AFAP1‐AS1 also has a metabolic impact on CRC.…”
Section: Discussionsupporting
confidence: 53%
“…AFAP1-AS1 was upregulated in almost all kinds of malignant tissues, such as lung cancer [ 24 , 25 ], breast cancer [ 16 , 26 ], and osteosarcoma [ 27 ]. Its upregulation had a significant impact on increasing malignancy and decreasing the survival of patients [ 28 ]. Primarily, overexpression of AFAP1-AS1 was found in TNBC tissues and cells, exerting oncogenic activity, and was associated with poor survival in TNBC patients [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…This result combined with the existing high level of expression, we found that AFAP1-AS1 had the possibility of promoting tumorigenesis. Previously, many papers have indicated that AFAP1-AS1 might act as oncogene in human cancers [13]. For example, in colorectal cancer, AFAP1-AS1 is notably increased, and AFAP1-AS1 knockdown inhibits the malignant behavior of cancer cells through targeting miR-195-5p/WISP1 axis [14].…”
Section: Discussionmentioning
confidence: 99%